Synthesis of doxorubicin-PLGA loaded chitosan stabilized (Mn, Zn)Fe2O4 nanoparticles: Biological activity and pH-responsive drug release - Montha, Wararat; Maneeprakorn, Weerakanya; Buatong, Nattha; Tang, I-Ming; Pon-On, Weeraphat (Materials Science & Engineering C, 2016)
We have synthesized Mn1−xZnxFe2O4 ((Mn, Zn) ferrite) magnetic nanoparticles (MNPs) having radius of 25nm to act as platforms for delivering drugs. The Mn0.9Zn0.1Fe2O4 MNPs exhibit superparamagnetic behavior with large saturation magnetization (MS). They were encapsulated in polymer so that they can be developed into PLGA-coated chitosan stabilized (Mn, Zn) MNPs, i.e., DOX-PLGA@CS@Mn0.9Zn0.1Fe2O4 which can serve as an effective carrier of the anti-cancer drug doxorubicin (DOX) whose release would be controlled by the pH in the environment surrounding the cancer tumor. The structure of the as-prepared particles is of a magnetic core-encapsulated by polymer shell layer of around 50nm thick. At a pH of 4.0, the DOX release within the first 5h is fast (around 57%). It becomes slower (around 46% over the next 25h) when the pH is increased to 7.4. The DOX-PLGA@CS@Mn0.9Zn0.1Fe2O4 (for concentrations lower than 125μgmL−1) shows lower toxicity against HeLa cells using DOX only. When the DOX-PLGA@CS@Mn0.9Zn0.1Fe2O4 is increased to 250μgmL−1, the DOX-PLGA@CS@Mn0.9Zn0.1Fe2O4 shows greater anti-cancer activity and has satisfactory therapeutic effect. The slow sustained release of the DOX by the drug loaded particles when they are in the physiological pH environment (7.4) of normal tissues and mild toxicity of DOX against cancer cell at low concentration point to the DOX loaded PLGA@CS@Mn0.9Zn0.1Fe2O4 being safely used for treating cancer. The higher dosage of DOX needed to kill the cancer cells will be released when the synthesized carriers are subject to the pH stimuli surrounding these cells. [Display omitted] •Synthesis of PLGA-coated chitosan stabilized (Mn,Zn) MCPs as an effective carriers.•The synthesized nanocarriers were found that the releasing depend on pH (pH-responsive).•In vitro biological activity revealed dose-dependent cytotoxicity.